Adipocyte metabolic response to Trypanosoma brucei in a co-culture setting - Pereira, Ana Raquel Santos (2022)
African trypanosomiasis is a vector-borne disease caused by extracellular protozoan parasites, including Trypanosoma brucei. The establishment of infection in mammalian hosts is characterized by invasion of the bloodstream and solid tissues. Among these, the adipose tissue (AT) is heavily colonized by T. brucei in mice. During infection there is also a large reduction of AT mass which suggests the mobilization of lipids stored in the adipocyte. However, it is not known how adipocyte to parasite interactions may contribute to adipocyte lipid metabolism. Here we show that co-culturing 3T3-L1 adipocytes and T. brucei in vitro increased adipocyte lipolysis. We found that this increase can be elicited by a soluble parasite factor, but it is larger when live parasites are in direct contact with adipocytes. Furthermore, chemical inhibition of adipose triglyceride lipase (ATGL) during co-culture lead to a reduction of fatty acid and glycerol release, indicating that the release of lipolytic products in the presence of T. brucei is an ATGL-dependent mechanism. Overall, the findings in this study indicate that T. brucei is able to directly modulate adipocyte catabolism, highlighting the need to further investigate the molecular partners involved in this host-parasite interaction.